MA`RIFAH : PENGERTIAN,TUJUAN KEDUDUKAN DAN TOKOH YANG MENGEMBANGKAN - Muhamad Iqbal Hidayat; M. Aufal Syahrul Abror; Maftuh Ajmain (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2025)
Ma’rifah is an important concept in the tradition of Islamic thought that refers to a deeper knowledge or understanding of God, the self, and the universe. In this context, ma’rifah is not only understood as theoretical knowledge, but also as a spiritual experience that leads to intuitive and inner awareness. The purpose of this journal is to discuss the various dimensions of ma’rifah in the perspective of Sufism and Islamic philosophy, and how this concept relates to achieving a servant's closeness to God. This article also explores the relationship between reason, heart, and revelation in the process of achieving ma’rifah, emphasizing the importance of personal experience in a Muslim's spiritual journey. In this discussion, the author refers to classical works and contemporary thought that raise the issue of ma’rifah, providing a more comprehensive perspective on its meaning and practice in everyday life. Thus, this study is expected to contribute to a deeper understanding of the concept of ma’rifah and its relevance in the context of contemporary Islamic spirituality